THE MONOMAJORITY ILLUSION: THE ROLE OF OLIGARCHIC DEPUTY GROUPS IN UKRAINE’S PARLIAMENTARY COALITION - Fisun, Oleksandr; Avksentiev, Anton (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2026)
The article examines the factional structure of the Verkhovna Rada of Ukraine in its IX convocation (2019-2026) and the role of oligarchic deputy groups in forming a hybrid parliamentary coalition. The dynamics of changes in the parliamentary structure are examined, with particular attention paid to the emergence of deputy groups in the Verkhovna Rada alongside party factions. Empirical evidence from marker votes (prime minister appointments and annual state budget approvals) demonstrates that, since 2021, the formal «monomajority» of the «Servant of the People» faction has been unable to independently secure the required quorum. It is shown that under these conditions, four oligarchic deputy groups – «For the Future», «Trust», «Platform for Life and Peace» and «Restoration of Ukraine» – act as stabilizers of the monomajority. The history of creation, formal leaders, and real beneficiaries of these groups has been analyzed. A distinctive feature of these groups is the absence of an electoral mandate, which exempts them from political accountability to voters. The conclusion is drawn that this hybrid coalition configuration lacks a programmatic-ideological dimension but is fully consistent with the patronal-client logic of the political regime. Political loyalty to the president as the «supreme patron» is exchanged by the deputy groups and their beneficiaries for protection of economic interests, business preferences, legal immunity, and other benefits. The historical continuity and structural reproducibility of this model are substantiated, where the presidential faction enters into informal alliances with oligarchic deputy groups to maintain control over parliament. Corresponding oligarchic deputy groups in the Verkhovna Rada of the VI–VIII convocations are identified – «Reforms for the Future», «Sovereign European Ukraine», «Economic Development», «People’s Will» and «Revival». It is noted that in the overwhelming majority of cases such deputy groups consist of «majoritarians». On this basis, the role of the mixed electoral system with a majoritarian component as a factor facilitating the formation of parliamentary coalitions in the interests of presidents is argued.